SERRANO-AMAYA, José Fernando. 2018. Homophobic violence in armed conflict and political transition. 1ª ed. New York / London: Palgrave Macmillan. 186 p. - Manuel Alejandro Rodríguez Rondón (Universidade do Estado do Rio de Janeiro, 2019)
Reseña: SERRANO-AMAYA, José Fernando. 2018. Homophobic violence in armed conflict and political transition. 1ª ed. New York / London: Palgrave Macmillan. 186 p.